Occurrence of a plasmid co-carrying cfr(D) and poxtA2 linezolid resistance genes in Enterococcus faecalis and Enterococcus casseliflavus from porcine manure, Italy. (15th December 2021) - Cinthi, Marzia; Coccitto, Sonia Nina; Fioriti, Simona; Morroni, Gianluca; Simoni, Serena; Vignaroli, Carla; Magistrali, Chiara Francesca; Albini, Elisa; Brenciani, Andrea; Giovanetti, Eleonora
Abstract: Objectives: To investigate the genetic elements and the transferability of linezolid resistance genes in three enterococci co-carrying cfr (D) and poxtA2 isolates from manure of a swine farm in central Italy. Methods: Two Enterococcus faecalis isolates and one Enterococcus casseliflavus isolate carrying both cfr (D) and poxtA genes were tested for their susceptibility to florfenicol, chloramphenicol, linezolid, tedizolid, tetracycline and vancomycin. Linezolid resistance genes transfer (filter mating), localization (S1-PFGE/hybridization), genetic elements and relatedness between isolates (WGS) were analysed. Results: Two E. faecalis isolates and one E. casseliflavus isolate carried the cfr (D) gene and the recently described poxtA2 variant. In the three enterococci, cfr (D) and poxtA2 were co-located on a 33 480 bp plasmid, pV386, 95%–100% identical (coverage 84%) to the Tn 6349 transposon of Staphylococcus aureus AOUC-0915. In all isolates, both genes also showed a chromosomal location. Same sequence identities were found from the comparison with currently known poxtA2 genetic elements. In the plasmid pV386, poxtA2 gene was not bounded by two IS 1216, as described in pIB-BOL, but closely associated to the cfr (D) and fexA genes. pV386 was always transferred by filter mating to Enterococcus faecium 64/3 recipient. Conclusions: The occurrence of the pV386 plasmid in E. faecalis and E. casseliflavus from swine manure is of great concern and highlights the need for control measures to contain its spread to other enterococcal species.